The Use of Social Media in Enacting Emotional Care to Elderly People During the Covid-19 Pandemic : Empirical Evidence from Rwanda - Irambeshya, Albert (University of Bayreuth African Studies Working Papers, 2023)
The paper examines the relevance of social media use by older people in their emotional care relationships with their kin living apart from them. Older people’s use of social media is still less visible in Rwanda and overlooked by researchers. The folk narrative in Rwanda considers social media usage a youth phenomenon. This paper goes beyond this consideration and shows how social media plays a significant role in care provision during crises like the COVID-19 pandemic. The research uses in-depth interviews of older people and their children to highlight social media’s usefulness in facilitating daily interactions. Since children could not travel to the village to visit their parents, social media allowed them to exchange with their older parents frequently calls and chats, which contained comforting words necessary for reducing the emotional stress created by the COVID-19 pandemic. Even if older people face the challenge of access to smartphones and digital literacy, using social media in enacting emotional care for older people proves to be indispensable in creating solid bonds, belongingness, and attachment to them.
Keywords: COVID-19; Digital media; Emotional Care; Family Interactions; Older people; Rwanda